Coffee Shop Experience Systematic Literature Review from 2002-2022 (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Coffee is an exciting drink because of its long history. A coffee shop is a place to gather and socialize. The coffee shops' growth is increasing because the coffee market continues to evolve. This study aims to examine the result of research in the context of coffee shops and the latest research related to the experience of coffee shops. Experience is a series of events that have been participated in. The phenomenon in the coffee industry is fascinating because of the growing number of coffee shops that are increasingly focusing on the quality of coffee beans because the world is entering the third wave of coffee. For this reason, this study tries to discuss journal articles related to experiences in coffee shops. The method used is to explore five research articles in the last four years, i.e., 2018-2022, connected to consumer experiences in coffee shops from Scopus-indexed journals. The researcher then tried to do a mapping based on the keyword experience from the articles in the Google Scholar database in the period 2002-2022 and got a total of 580 papers. The results of this study are a discussion of the latest five articles from Scopus-indexed articles and mapping with VOSviewer software for research articles taken from the Google Scholar database within 20 years. This literature review can be a guide and reference for research related to the theme of consumer experience in the context of coffee shops.